Temperature, Salinity, pH, oxygen and chlorophyll measurements in the Oddewatt oyster reef in 2021 - K Mathias Wegner (PANGAEA, 2022)
Temperature, Salinity, pH, oxygen and chlorophyll data was collected with a Hydrolab HL7 multi parameter sonde installed on an oyster table in the Oddewatt oyster reef in Königshafen, Sylt, Germany (55.028483, 8.433876). The table and sonde surface during low tide.